The impact of the COVID-19 pandemic on telework and short sickness absences among Finnish knowledge workers - Ropponen, Annina; Haapakangas, Annu (Frontiers in Public Health, 2025)
IntroductionLongitudinal studies are rare for associations between telework and sickness absence (SA). This prospective cohort study aimed to investigate short (1–3 days) SA from 2019 to 2023 among a cohort of Finnish knowledge workers and the role of telework in short SA.MethodsComplete employer-owned register data on SA and telework were available from four organizations for 2019–2023, comprising 924 employees. Weekly means of telework days/week and short (1–3 days) SA days were calculated and analyzed using conditional Poisson with fixed-effects to obtain incidence rate ratios (IRRs) with 95% confidence intervals (CIs).ResultsThe levels of short SA were low from 2019 to 2023, while telework increased at the start of the COVID-19 pandemic and remained at an elevated level. In a fully adjusted model, each 1-day increase in telework was associated with a higher likelihood of short SA (IRR 1.35, 95%CI 1.22, 1.50).ConclusionTelework has become a central way of working among Finnish knowledge workers since the COVID-19 pandemic, while shortSA has remained at a low level. A higher number of weekly teleworking days may be linked to a higher likelihood of short SA, indicating that workplaces should pay special attention to their employees’ wellbeing and health.